A new genus of scolopendrid centipede (Chilopoda: Scolopendromorpha: Scolopendrini) from the central Australian deserts - Waldock, Julianne; Edgecombe, Gregory D. (Zootaxa, 2012)
The first new species of Scolopendridae discovered in Australia since L.E. Koch’s comprehensive revision in the 1980sis named as a new monotypic genus of the Tribe Scolopendrini, Kanparka leki n. gen. n. sp. Its distribution includes theGibson and Little Sandy Deserts in Western Australia and the western part of the Tanami Desert in the Northern Territory.The new genus is especially distinguished from other scolopendrines by the spinulation of its robust ultimate legs, partic-ular the presence of spines on the femur and tibia in addition to the predominantly irregularly scattered spines on the prefe-mur. Cladistic analysis based on morphological characters resolves Kanparka in a clade with Scolopendra, Arthrorhabdus, Akymnopellis and Hemiscolopendra, within which Scolopendra is non-monophyletic.